2015
DOI: 10.1016/j.canlet.2014.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Tumor matrix protein collagen XIα1 in cancer

Abstract: The extracellular matrix is increasingly recognized as an essential player in cancer development and progression. Collagens are one of the most important components of the extracellular matrix, and have themselves been implicated in many aspects of neoplastic transformation. Collagen XI is a minor collagen whose main physiologic function is to regulate the diameter of major collagen fibrils. The α1 chain of collagen XI (colXIα1), has known pathogenic roles in several musculoskeletal disorders. Recent research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 53 publications
3
74
0
1
Order By: Relevance
“…A chemoresistance study reported that downregulation of COL11A1 suppressed chemoresistance in epithelial ovarian carcinoma [28]. Many studies had highlighted the importance of COL11A1 in multiple types of cancer, including colorectal, ovarian, breast, head and neck, lung, and brain cancers [29]. COL11A1 was not reported as a driver gene in previous ESCC genome studies.…”
Section: Resultsmentioning
confidence: 99%
“…A chemoresistance study reported that downregulation of COL11A1 suppressed chemoresistance in epithelial ovarian carcinoma [28]. Many studies had highlighted the importance of COL11A1 in multiple types of cancer, including colorectal, ovarian, breast, head and neck, lung, and brain cancers [29]. COL11A1 was not reported as a driver gene in previous ESCC genome studies.…”
Section: Resultsmentioning
confidence: 99%
“…The gene mutations of structural protein collagen XIaI has been well investigated in musculoskeletal disorders, such as type II Stickler syndrome and Marshall syndrome. 18,19 It is noteworthy that COL11A1 may serve as a promising putative tumor marker due to its barely-existing character in most tissues. 18 In this study, we found that COL11A1 was not only amplified, but also prone to mutating in many types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…COL11A1 encodes the α1 chain of collagen XI, a minor fibrillar collagen expressed by chondrocytes and osteoblasts but not quiescent fibroblasts [25, 26]. The absence of functional collagen XI leads to abnormally thickened cartilage and tendon fibrils, suggesting the role of collagen XI in maintaining proper fibril diameter [27, 28].…”
Section: Introductionmentioning
confidence: 99%
“…The absence of functional collagen XI leads to abnormally thickened cartilage and tendon fibrils, suggesting the role of collagen XI in maintaining proper fibril diameter [27, 28]. Studies have demonstrated that COL11A1 mRNA is markedly elevated in cancers of the oral cavity/pharynx, head and neck, breast, lung, esophagus, stomach, pancreas, colon, and ovary, but not in matched normal tissues (reviewed in [25, 26]). COL11A1 has been identified as part of gene signatures associated with adverse clinical outcomes including resistance to neoadjuvant therapy in breast cancer [29], time to recurrence in glioblastoma [30], poor survival in kidney cancer [31], and time to recurrence and overall survival in ovarian cancer [32, 33].…”
Section: Introductionmentioning
confidence: 99%